ETHICS AND CYBERSECURITY ARE NOT MUTUALLY EXCLUSIVE. Issue 1 (3rd July 2019) - Shoemaker, Dan; Kohnke, Anne; Laidlaw, Greg
Abstract: Ethics is probably the last topic that anybody thinks about when planning a cybersecurity response. Still, the organization's honest commitment to the confidentiality, integrity and availability of its data depends entirely on how it views its ethical responsibilities. So, in many respects ethics underlies everything. To this point there has been no commonly accepted basis for establishing an ethical stance regarding cybersecurity. The CSEC2017 model provides that basis now. This article will outline the ethical factors related to cybersecurity as recommended by the model and discuss how they apply in the creation of a practical response.